The Road to Recovery #5: Self-Assessment of Virtual Facilitation to Build Trust - Colby Jordan Silvert; Cody Gusto; John Diaz; Glenn Israel (EDIS, 2021)
This fifth publication in the Road to Recovery series discusses how Extension professionals can evaluate techniques to build trust when facilitating virtual programming. Specific recommendations are provided addressing concerns about short- and long-term virtual trust, inclusion techniques, Zoom fatigue, and cybersecurity. This new 5-page publication of the UF/IFAS Department of Agricultural Education and Communication was written by Colby Silvert, Cody Gusto, John Diaz, and Glenn Israel. https://edis.ifas.ufl.edu/wc388